Effects of celecoxib in human retinoblastoma cell lines and in a transgenic murine model of retinoblastoma. Issue 9 (19th August 2005) - Tong, C T; Howard, S A; Shah, H R; Van Quill, K R; Lin, E T; Grossniklaus, H E; O'Brien, J M
Abstract : Background/aim: Celecoxib, a cyclooxygenase-2 inhibitor and antiangiogenic agent, has demonstrated potent anticancer effects in preclinical studies and in human clinical trials. To evaluate the potential utility of this agent in the treatment of retinoblastoma, the authors investigated the effects of celecoxib in retinoblastoma cell lines and in a murine model of this disease. Methods: Growth inhibitory effects of celecoxib were evaluated in Y79 and Weri-RB1 human retinoblastoma cell lines by WST-1 cell proliferation assay. For animal study, two groups of 24, 8 week old LHβ- TAg transgenic mice were treated with celecoxib (250 mg/kg, orally once a day) or vehicle control, 5 days/week for 6 weeks. Mice were sacrificed on day 43. Enucleated eyes were serially sectioned and ocular tumour burden was quantified by histopathological analysis. Results: Celecoxib did not inhibit proliferation of Y79 or Weri-RB1 cells, even at concentrations far exceeding clinically achievable levels. No significant difference in ocular tumour burden between celecoxib treated and control mice (p = 0.73) was found. Conclusion: Celecoxib was ineffective at inhibiting proliferation of retinoblastoma cells in vitro and was ineffective at controlling retinoblastoma tumour growth in a murine model of this disease. On the basis of these findings, oral celecoxib therapy is unlikely to have clinical utility in the treatment of retinoblastoma.